The nurse’s role in preventing delirium in critically ill adult/elderly patients - Oliveira, Cláudia; Nobre, Cátia Filipa Garnacho Martins; Marques, Rita Margarida Dourado; Mendes, Maria Manuela Madureira Lebre; Sousa, Patrícia Cruz Pontífice (Revista Cuidarte, 2022)
Introduction: Delirium is an acute brain dysfunction, associated with increased mortality and morbidity, which often affects critically ill adult/elderly patients. Nurses have a crucial role in the prevention/control of delirium, through the implementation of non-pharmacological interventions. Objective: To know the nursing interventions in the identification, prevention and control of delirium in adult/critical elderly patients. Materials and Methods: An Integrative Literature Review of articles published between 2014 and 2018 was carried out, which identified nursing interventions aimed at the prevention and control of delirium in adult/critical elderly patients. Four searches were carried out, in the electronic databases of EBSCOhost and B-on. Results: 13 studies were identified, which present nursing interventions, mostly non-pharmacological, for the prevention and control of delirium in adult/critical elderly patients. Of these, interventions related to the environment, sleep promotion, early therapeutic intervention, cognitive assessment and patient orientation, interventions systematized in protocols, as well as interventions aimed at the participation of family members, the training of nurses and the teaching of patients are evident. Risk factors for the development of delirium and assessment tools were also identified. Discussion: The prevention of delirium is important and imperative, since its occurrence in critically ill patients is associated with increased mortality, morbidity, length of stay and a high hospital cost. The identification of risk factors for the occurrence of delirium should be included in delirium management protocols. Conclusions: Evidence has shown that nurses are essential in the early identification, prevention and control of delirium, preventing the progression of the disease, contributing to the reduction of morbidity and mortality. The nursing intervention must include the identification of predisposing and/or precipitating factors to contribute to the reduction of the occurrence and/or resolution of delirium. How to cite this article: Oliveira Cláudia; Garnacho Martins Nobre Cátia Filipa; Dourado Marques Rita Margarida; Madureira Lebre Mendes Maria Manuela; Cruz Pontífice Sousa Patrícia. O papel do enfermeiro na prevenção do delirium no paciente adulto/idoso crítico. Revista Cuidarte. 2022;13(1):e1983. http://dx.doi.org/10.15649/ cuidarte.1983